Impact Analysis of Academic Guidance and Training Soft Skill to Improve Student's Self-Concept and Independence Through Tuweb - Barokah Widuroyekti; ‪Dian Ratu Ayu Uswatun Khasanah; Binti Isrofin; Jahyu Hartanti; Dwikoranto Dwikoranto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The implementation of learning activities during the pandemic is carried out online, including learning activities at the Distance Learning Program Unit of the Open University of Semarang using Web-based Tutorials (Tuweb) using Microsoft Team. Online learning requires students to study independently. The purpose of this study was to integrate the impact of user experience, academic self-concept and adversity quetion on independent learning in students. This type of research is quantitative research. Data collection techniques using a psychological scale. The psychological scale used in this study is (1) the learning independence scale. (2) academic self-concept scale (3) adversity quotient scale and (4) user experience scale. The measurement results show a TLI of 0.955. This output shows the accuracy, consistency of the accuracy of the composite reliability measuring instrument which shows the accuracy, consistency of the accuracy of a measuring instrument in making measurements. Student independence is influenced by academic self-concept and user experience, but the adversity quotient does not have a significant effect.